Does the flirting behaviour of a selection of black South African youths differ from Western perspectives on flirting - Franzel Du Plooy-Cilliers; Linda Venter (Communicare, 2022)
Research shows that flirting is found in all cultures and societies. However, very little research has been conducted on the differences in the courtship and flirting behaviour of people from diverse cultures. Like all other communication behaviour, flirting behaviour varies from culture to culture, and acceptable flirting behaviour in one culture might be viewed as inappropriate in another. Likewise, because all forms of communication are dynamic, generation gaps may lead to conflict as a result of differences in opinion about the appropriateness of certain behaviours. Thus, the patterns of flirting behaviour are culture-specific and even generation-specific. Although there are research findings available on flirting behaviour in Western and Eastern cultures, very few scholars have researched flirting behaviour in African cultures. This article provides a brief summary of existing research findings. In order to gain insight into culture-specific views and opinions, a qualitative research design in the form of focus group interviews with a selection of black South African youths was utilised. The primary aim of the study is to explore the similarities and differences between the flirting behaviour of a selection of South African youths from an African background and Western research findings on flirting behaviour. Secondary aims are to explore whether some black South African youths’ perceptions of acceptable flirting behaviour differ from their interpretation of their parents’ views, and to utilise a qualitative research design in order to identify useful and appropriate variables that could be tested quantitatively in follow-up studies. It is cautiously concluded that there are both similarities and differences between the reported flirting behaviour of South African youths from an African background and Western research findings on flirting behaviour. Furthermore, most of the participants indicated that the flirting behaviour they exhibit is unlikely to be viewed as proper behaviour by their parents